CULTURAL HISTORICAL ACTIVITY THEORY: EXPLORING PRINCIPALS' INSTRUCTIONAL LEADERSHIP - (:unkn) unknown (CENTRAL BOHEMIA UNIV, 2016)
Instructional leadership activities are significant for school development. Although many researchers in this field consider leadership activities relating to the work of school principals, in effect, leadership is a network activity that includes all school staff. This study aims to show this interdependence network activity within Cultural Historical Activity Theory. The research question is what are the activities of an instructional leader? in order to understand instructional leadership activities in school from perspectives of Turkish graduate students and Cultural Historical Activity Theory. The answers are conceptualized within the framework of an Activity Theory. The students were asked to write about the activities of an instructional leader in the first and last course of the semester. Eighteen graduate students participated in this study.
Keywords: Cultural Historical Activity Theory; instructional leadership; principals